Flux pinning in superconducting multilayer 2H-NbSe2 nano-step junction - Minseong Kwon; Mingi Kim; Yoonji Gong; Heeyeon Lee; Young Duck Kim (Materials for Quantum Technology)
Superconductors exhibit dissipationless supercurrents even under finite bias and magnetic field conditions, provided these remain below the critical values. However, type-II superconductors in the flux flow regime display Ohmic dissipation arising from vortex dynamics under finite magnetic fields. The interplay between supercurrent and Ohmic dissipation in a type-II superconductor is dictated by vortex motion and the robustness of vortex pinning forces. In this study, we present an experimental investigation of the superconducting phase transitions and vortex dynamics in the atomically thin type-II superconductor 2H-NbSe _2 . We fabricated a high-quality multilayer 2H-NbSe _2 with a step junction, demonstrating supercurrent in clean limit below a critical temperature of 6.6 K and a high residual resistance ratio of 17. The upper critical field was estimated to be 4.5 T and the Ginzburg–Landau coherence length 8.6 nm. Additionally, we observed phase transitions induced by vortex viscous dynamics in the 2H-NbSe _2 step junction. Analysis of the pinning force density using the Dew-Hughes model indicates that the pinning force in the 2H-NbSe _2 device can be attributed to step junction, related to the surface-Δ κ type of pinning centers. Our findings pave the way for engineering pinning forces by introducing artificial pinning centers through partial atomic thickness variation in layered 2D superconductors while minimizing unwanted quality degradation in the system.